Pandemic Pivot: Unraveling the Digital Fashion Frontier on Shopee - Lintang, Lusitania (Ilomata International Journal of Management, 2024)
During the COVID-19 pandemic, there has been a major shift in people's activities and behaviors, which are moving towards the digital world. This helps people in their daily lives, both as buyers and business people in various industries, including the fashion industry. The fashion industry itself is a sector of multinational companies that have a high-net-worth value, whose focus is mainly on designing, producing, and marketing clothes to the public. Online shopping digital platforms such as Shopee are one of the main choices for people in making shopping transactions today. The purpose of this study was to find out online consumer reviews, social media advertisement, and influencer endorsements can influence people's online purchase intention for fashion stores on the Shopee platform. The research used a non-probability sampling approach, specifically choosing the convenience sampling technique during the sample selection process. The number of samples used in the study was 130 respondents, and data collection was conducted by distributing questionnaires through Google Forms. The data analysis was conducted using the Structural Equation Modelling (SEM) program SmartPLS 4.0. The research shows that social media ads on Shopee in Jabodetabek significantly impact online purchase intentions. Influencer engagement also influences intentions positively, although not statistically significant. Online consumer reviews and purchase intention variables share similarities, both influenced by external factors. Businesses should tailor advertising strategies for optimal performance and leverage social media effectively to thrive in e-commerce.